From Cyclical Apocalypse to Anthropocene Anxiety: Notes From a Research Project on Anglophone Climate- Change Literature - Mundler, Helen (International Transitions, 2024)
This article starts from the basis that the study of clifi, or climate-change fiction, can be considered a legitimate part of AEI-International School’s ongoing interdisciplinary research focus on International Transitions. The transitions described in clifi at the level of event are correlated with transitions in novelistic form, and also in the very idea of what constitutes clifi. Firstly, this article establishes the pragmatic “usefulness” of clifi as a means to mirror the current realities of a world changed by climate emergencies, as well as to anticipate future trends and models. It then moves on to focus, secondly, on the apparent paradox inherent to clifi as a novelistic genre: that is, that in portraying apocalypse and the end of the world, it also posits the renewal of language and of novelistic form. Reference is made to James Berger’s idea of apocalypse as the condition of symbolisation and creativity, following the postmodern exhaustion with which it was threatened in the last decades of the twentieth century. Thirdly, an analysis of the last chapters of Margaret Atwood’s Maddaddam trilogy shows that the literary object, above all, is saved from “the flood” of climate change and its concomitant disasters, to be carried forward into deep time which transcends human culture, but which will continue to be imbued with it. Finally, current developments in the concept of what constitutes clifi are analysed through the original concept of Anthropocene Anxiety.